(3QSGdI aj Yde GdNWs - (3UGdM Hf jMji GdehUdjs
(3ChdgG (B:s
(3Yde GdNW Yde jHMK ajg Yf cjajI cJGHJI GdCdaGX s
(3BNQgG (B:s
(3dCfg CfSH He bHdg ef GdfbW hGdTcd GdePchQ aj Yde GdNW hGdMOjK CjVkG s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI GdMceI (B- (3HZOGO (B(95) s
Keywords: (3GdNW hCdGJgs